Policy conflicts and factors affecting conflict resolution in South Korea: Trends from the Korean public policy conflict database (1948-2014). Issue 1 (18th September 2019) - Lim, Dong-Jin; Kwon, Kyung Deuk
Abstract : Purpose: This paper aims to identify and explore the overall frequency and characteristics of policy conflicts, with a focus upon those factors affecting conflict resolutions in South Korea. Design/methodology/approach: The study uses data from cases of conflict from the Korean Public Policy Conflict Database (KPPCDB) (1948-2014). For the analysis of data, chi-squared test and multinomial logistic regression are used. Findings: The findings show a total of 2, 030 policy conflicts in 1948-2014, most of which were conflicts of interest (47.9 per cent). More than 70 per cent (71.2 per cent) were policy conflicts between the government and the private sector; the field with the most policy conflicts was regional development (21.0 per cent), and 84.1 per cent of all policy conflicts were resolved. The factors that affected conflict resolution by interest were conflicts between the government and private sector, authoritarian government, national regions and capital areas. Practical implications: This paper suggests reforming the current procedures of conflict management, adopting alternative dispute resolutions, and developing a social-consensus-building process for efficiently resolving conflicts. Originality/value: This study built a database (KPPCDB) examining 66 years of conflict cases that took place between 1948, the year the Korean Government was established, and 2014. This database covers all cases of policy conflicts that occurred in Korea and provides a comprehensive understanding of the phenomena of policy conflicts and conflict resolution.